Strategi Pendidikan Islam Bagi Masyarakat Perkotaan: Studi Analisis Pemerataan Pendidikan di Denpasar, Bali - Muhammad Shodiq; Alaika M. Bagus Kurnia PS (Labor Program Studi Pendidikan Sosiologi, 2024)
This research aims to examine more deeply how the role of Islamic education in showing the existence of equal education in Muslim minority areas. The research in this article is qualitative research. By using literature study data collection and several documents from statistical institutions in the city of Denpasar Bali. The analysis technique in this research, using case study analysis techniques. So as to be able to suppress some of the problems of equalization of education by using John Rawls' theory of social justice. The formulation of the problem is, How is the Condition of Denpasar Society Regarding Education Equality? Second, what is the condition of Islamic education equity in Denpasar? And the third is, how is the role of Islamic education in continuing the equalization of education in Denpasar? So that the definition of equity has a different pattern in the perspective of Islamic education.